Monday mourning eaudiobook A novel. - Reichs, Kathy (Temperance Brennan, 2004)
Internationally acclaimed forensic anthropologist and New York Times bestselling author Kathy Reichs explores Stockholm syndrome—the psychology of a captive submitting to the ideology of a captor—in this mesmerizing new thriller. The bones of three young women are unearthed in the basement of a Montreal pizza parlor, and forensic anthropologist Tempe Brennan has unsolved murder on her mind as she examines the shallowly buried remains. Coming up against a homicide cop who is convinced the dead have been entombed on the site for centuries, Tempe perseveres, even as her own relationship with Detective Andrew Ryan is at a delicate turning point. In the lab, the clean, well-preserved bones offer few clues. But when carbon-14 dating confirms her hunch that these were recent deaths despite the antique buttons found near the bodies, Tempe finds herself drawn deep into a web of evil from which there may be no escape. Women have disappeared, never to return...and she may be next.